Study on the Design of Tall Building Escape Device based on Escapement Mechanism - Zhang Liping (Jixie chuandong)
Through alternate engage of the escapement wheel and escapement fork,the escape device based on escapement mechanism can release uniformly gravitational potential energy of body to make the body land safely to the ground in a certain average speed. The transmission scheme of the device is designed. The parameters design and structural design of escapement mechanism are completed. The mathematical model of dynamics analysis is established for escapement mechanism. It proves that the rate of decline of the evacuee of tall buildings is proportional to the square root of body weight,and inversely proportional to the square root of rotational inertia of escapement fork and the balance. The rotational inertia of the balance is calculated according to the case the rate of decline of the body to be 2 m / s.